Water for the urban poor: Balancing financial and social objectives through service differentiation in the Kenyan water sector. (October 2017) - Schwartz, Klaas; Tutusaus, Mireia; Savelli, Elisa
Abstract: Kenyan water utilities face a challenge of balancing the financial objective of commercial viability with the social objective of service expansion. To achieve this, they employ service differentiation in which different categories of consumers receive different levels of service. Although service differentiation has achieved results, it reflects a prioritization of financial objectives over social objectives and raises three particular concerns. First, service differentiation reflects a withdrawal of the utility from core service provision responsibilities. Second, it results in inequitable service provision. Finally, it may lock low-income consumers into a low level of service. Highlights: Service differentiation is to serve both the utility and the low-income consumer. Although service differentiation has achieved results it has lead to a prioritization of financial over social objectives. Service differentiation leads to concerns about utility withdrawal from service provision responsibilities. It also raises questions about inequitable service provision and infrastructural lock-in of low-income consumers.